Effect of solvent used for isocyanate primer on interphase formation. Issue 16 (10th December 2021) - Sensui, K.; Tarui, T.; Sato, C.
ABSTRACT: The application of primer is one of the most widely used pre-treatments to improve adhesion. However, few studies on the adhesive mechanism have investigated the effect of the organic solvent used for the primer on the improving of adhesion strength. In this study, attenuated total reflection infrared spectroscopy was performed to evaluate the interphases of multiple primers with different organic solvents for dilution. The main conclusion of this work is that the interphase thickness depends on the relative permittivity and viscosity of the organic solvent used for the primer.